2009
DOI: 10.1007/s11664-009-0802-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Transit-Time Limitations of the Impulse Response in Mid-Wave Infrared HgCdTe Avalanche Photodiodes

Abstract: The impulse response in frontside-illuminated mid-wave infrared HgCdTe electron avalanche photodiodes (APDs) has been measured with localized photoexcitation at varying positions in the depletion layer. Gain measurements have shown an exponential gain, with a maximum value of M = 5000 for the diffusion current at a reverse bias of V b = 12 V. When the light was injected in the depletion layer, the gain was reduced as the injection approached the N+ edge of the junction. The impulse response was limited by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 17 publications
(18 reference statements)
3
32
0
Order By: Relevance
“…10 The modeled fundamental, carrier transit time limited, BW is greater than 10 GHz. 22 Linear mode HgCdTe e-APDs as fabricated at DRS are front-side illuminated cylindrical p/n−/n+ HgCdTe homojunction photodiodes in the HDVIP ® (HDVIP ® stands for "high-density vertically integrated photodiode.") configuration, as shown in Fig.…”
Section: Calculations For Hgcdte Linear Mode Avalanche Photodiode Cammentioning
confidence: 99%
“…10 The modeled fundamental, carrier transit time limited, BW is greater than 10 GHz. 22 Linear mode HgCdTe e-APDs as fabricated at DRS are front-side illuminated cylindrical p/n−/n+ HgCdTe homojunction photodiodes in the HDVIP ® (HDVIP ® stands for "high-density vertically integrated photodiode.") configuration, as shown in Fig.…”
Section: Calculations For Hgcdte Linear Mode Avalanche Photodiode Cammentioning
confidence: 99%
“…However, they reported that the planar APD structure provides fill factor~ 100 % and the collection efficiency > 90%, whereas HDVIP diode has advantage to yields low dark current, high quantum efficiency and high operability. 39,47 . They are first to measure the impulse response time for front side illuminated n-on-p MWIR HgCdTe e-APD at 77 K with λ = 1.55 μm laser pulse 47 .…”
Section: Development Of Hgcdte Based Apd Device Technologymentioning
confidence: 99%
“…1, such high bandwidths has not yet been achieved in HgCdTe APDs due to slow carrier collection through diffusion and/or impedance mismatch (BW=40-600 MHz). Impulse response-time measurements have however shown that bandwidths of 10 to 20 GHz should be achievable in SWIR and MWIR APDs designed for fast response [10,12].…”
Section: Hgcdte Apds Characteristicsmentioning
confidence: 99%
“…The latter is again related to exclusive electron multiplication, which guarantees that the response time is limited by a single transit time of the depletion region width for each type of carrier [9]- [12]. The experimental and numerical studies of the carrier dynamics during the multiplication suggests that bandwidths in the range of 10-30 GHz should be achievable in HgCdTe APDs at gains higher than 100, although the highest bandwidth so far is in the range of 600 MHz to 1 GHz [10,12] . These characteristics are complemented by a high gain homogeneity which makes HgCdTe APDs suitable for imagery application.…”
Section: Introductionmentioning
confidence: 99%